OPTIMIZING ENERGY CONSUMPTION FOR WIRELESS SENSOR NETWORKS - Lại Thị Nhung; Nguyễn Thị Hòa; Lê Đăng Nguyên; Nguyễn Gia Như; Đặng Thanh Hải (Tạp chí Khoa học Đại học Đà Lạt)
In wireless sensor networks, sensors are deployed and aim to gather information from the target area. The information collected by the sensors will be transmitted to the base station by radio waves. From here, the data is analyzed and processed to make decisions. One of the problems of the wireless sensor network is the need to save energy consumption, extending the life of the network. In this paper, we propose a solution for deploying sensor networks by clustering and combining cluster head selection to optimize power consumption and extend the life of the network. Comparative analysis of algorithms proposed with traditional clustering algorithms LEACH, LEACH-C, K-Mean and FCM will confirm the effectiveness of the proposed solution.